Common Fixed-Point Theorems in the Partial b-Metric Spaces and an Application to the System of Boundary Value Problems. (23rd September 2021) - Nazam, Muhammad; Hamid, Zahida; Al Sulami, Hamed; Hussain, Aftab
Abstract : In this paper, we investigate the conditions for the existence of the common fixed points of generalized contractions in the partial b -metric spaces endowed with an arbitrary binary relation. We establish some unique common fixed-point theorems. The obtained results may generalize and improve earlier fixed-point results. We provide examples to illustrate our findings. As an application, we discuss the common solution to the system of boundary value problems.